KESELAMATAN TRANSPORTASI JALAN DI INDONESIA SAATNYA ADA PERUBAHAN - Sulistio, Harnen (Jurnal Transportasi, 2008)
AbstractÂ This paper describes the implementation of road safety strategy that was experienced in many developed countries, whereby the sustainable road transport issues were included. Such strategy can hardly be found in Indonesia, the country that facing with serious problem in road accidents. Road safety action plans, those carried out to mitigate road accidents in some countries, were presented. In addition the paper also suggested the actions have to be taken to make better road accidents situation in Indonesia.Â Keywords: road safety strategy, road accidents, action plans